Primary left atrial angiosarcoma mimicking severe mitral valve stenosis. Issue 4 (16th March 2005) - Engelen, M; Bruch, C; Hoffmeier, A; Kersting, C; Stypmann, J
Abstract : Primary cardiac tumours are quite rare and most of these tumours are benign. In this report, a patient presented with heart failure symptoms attributable to severe mitral valve stenosis. Echocardiography showed a dense left atrial mass causing functional mitral valve obstruction. The morphological and intraoperative presentation was highly suggestive of a myxoma but histopathological examination found a primary pedunculated cardiac angiosarcoma. The role of two dimensional and transoesophageal echocardiography in the assessment of cardiac masses and tumours is discussed.